Legally Buddhist: monks, nuns, and legal texts in Dunhuang - Liu, Cuilan ca. 20./21. Jh. (Studies in Chinese Religions, 2020)
Manuscripts found in the Dunhuang cave 17 inform us that ordained Buddhist monks and nuns in Dunhuang had been actively engaged in legal practices in this region as plaintiffs, defendants, witnesses, mediators, and representatives in the trial of various disputes. This article examines the colophons on Chinese manuscripts of Buddhist monastic law (Vinaya) to explore the ways in which ordained Buddhists had contributed to production and preservation of legal texts in Dunhuang. It reveals that contrary to rules in the Indian Buddhist monastic law that restrict access to the monastic law exclusively to fully ordained Buddhist monks and nuns, both lay and ordained Buddhists in China not only had access to copies of Buddhist monastic law texts from various traditions but had also volunteered or were commissioned to copy them. In Dunhuang, the transmission of legal knowledge benefited from the practice of lay and ordained Buddhists who had aspired to copy, sponsored the copying, or preserved Buddhist monastic law texts for reasons varying from curing illness to benefiting the sentient beings and accumulating merits for the deceased.